Metamatrial-based Antipodal Vivaldi Wearable UWB Antenna for IoT and 5G Applications - Saeidi, T. (Institute of Electrical and Electronics Engineers Inc., 2020)
When 4G showed several limitations on data rate transition and the required BW for communication increased day by day, a new alternative has been sought to compensate those drawbacks. Therefore, scientists suggested sub-6G (5G) and 6G to improve communications limitations. This paper presents an antipodal Vivaldi metamaterial-based flexible wearable ultrawideband (UWB) antenna for sub-6G, internet of things (IoT), and wireless body area network (WBAN) applications working at the range of 4.25-35 GHz. The miniaturized proposed antenna (15 Ã 10 mm2) comprises a layer of denim with h= 0.7 mm and the resonator made of ShieldIt. A modified leaf-shaped antipodal patch is developed to have a broad bandwidth with high directive gain and high efficiency to be an acceptable candidate for sub-6G communications. First, the patches are cut by two half-circle arcs, two stubs at the front and two L-shape slots at the back to improve the radiation efficiency of the antenna while suppressing the undesired surface waves. Then, the antenna is loaded with the proposed metamaterial arrays to extend the bandwidth (BW) and enhance the gain and directivity of the antenna utilizing a semiflexible Rogers 5880 substrate (h=0.508 mm). Besides, all the antenna's parts are optimized and formed to obtain maximum directive gain and radiation efficiency of 8.97 dBi and 98 , respectively. The good agreement between simulation and measurement results proves the antenna capability in working for sub-6G, IoT, and WBAN applications. Â© 2020 IEEE.